2022
DOI: 10.1111/irv.12991
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza in children: Costs for the health system and society in Europe

Abstract: Background Pediatric influenza causes significant morbidity annually, resulting in an increased economic burden. Therefore, we aimed to summarize existing literature regarding the costs of pediatric influenza in Europe, paying particular attention to the direct and indirect costs considered in the economic evaluations. Knowing health and social costs of childhood influenza is essential to support value‐based health decisions to implement effective immunization strategies. Methods We searched three databases fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 51 publications
(146 reference statements)
1
24
0
1
Order By: Relevance
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Among the European studies, eight (36.4%) were conducted specifically in Italy [ 3 , 4 , 13 , 31 , 38 , 39 , 43 , 47 ]. In addition, of the 40 articles included in our work, 17 (42.5%) were systematic reviews or literature reviews [ 3 , 5 , 10 , 11 , 12 , 22 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 37 , 41 , 47 , 48 ], ten (25%) were economic evaluations [ 8 , 13 , 19 , 21 , 23 , 26 , 27 , 34 , 44 , 45 ], seven (17.5%) were cross-sectional studies [ 18 , 35 , 36 , 38 , 42 , 43 , 49 ], two studies (5%) were HTA reports [ 4 , 39 ], one study (2.5%) was a nonlinear regression model [ 33 ], and three studies (7.5%) were expert opinions [ 20 , 40 , 46 ]. The main features of the studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations